New cleft lip and palate classification of severity from Outreach Surgical Center - Rossell Perry, Percy (2006)
The current classifications for cleft lip and palate are descriptions of the components involved in the cleft but, they dont consider the severity of its distortion. The severity of the cleft is one of the most important elements to be considered in the presurgical planning. The use of presurgical orthopedy and modifications of classic surgical techniques, are examples of individual management of the more severe forms of cleft lip. This work shows the design of a new classification of cleft lip based in degrees of severity of the three cleft lip and palate components: nasal, lip and palate. The methodology used was the revision of surgical results obtained from 1043 cleft lip and palate patients operated by us, under the protocol design based in this severitys classification between 1996 and 2005. We did the estimation of the surgical results through the number of cases with major surgical revision and follow ups at least within one year. This protocol includes a new scheme of description of cleft lip and palate and new modification of Millards technique.